Development of Goal Management Training+ for Methamphetamine Use Disorder Through Collaborative Design - Anderson, Alexandra C.; Robinson, Alex H.; Potter, Eden; Kerley, Bronte; Flynn, Daphne; Lubman, Dan I.; Verdejo-García, Antonio (Frontiers in Psychiatry, 2022)
Background Methamphetamine use disorder (MUD) is associated with executive dysfunctions, which are linked with poorer treatment outcomes including earlier drop out and relapse. However, current treatments for MUD do not address executive functions. Goal Management Training (GMT) is an evidence-based cognitive remediation program for executive dysfunction, although required modifications to enhance its relevance and application within addiction treatment settings. This study aimed to 1) tailor GMT to the key cognitive deficits and typical treatment duration of MUD; 2) explore consumers’ (people with MUD) engagement with the revised program; 3) implement a prototype of the program with consumers; and 4) present the manualized standard administration to clinical service providers. Methods We followed the Medical Research Council Complex Interventions Framework and employed an evidence- and person-based intervention development process. We used a four-phased approach and collaborated with neuropsychology experts, design researchers in healthcare, consumers with MUD, and clinical service providers. Each aim was addressed in a separate study phase; including content refinement and review with neuropsychology experts (phase 1), intervention design and collaboration with consumers (phase 2), prototype development and review with consumers (phase 3), and final program modifications and review with clinical stakeholders (phase 4). Results Findings from phase 1 indicated support for targeting four cognitive processes (attention, impulse control, goal setting, and decision-making). Key feedback included the need to help habitualize cognitive strategies and to guide consumers in applying these strategies in emotionally salient situations. Findings from phases 2 and 3 indicated consumer support for the program strategies and materials but highlighted the need to further enhance the personal relevance of specific content and journal activities. Findings from phase 4 provided clinicians support for the revised program but indicated an opportunity to minimize unintended effects. We present the intervention materials for the final revised program, Goal Management Training+ (GMT+), in line with TIDieR guidelines. Conclusions GMT+ targets key cognitive processes and is sensitive to the clinical needs of people with MUD. Our intervention development process was important for informing the active ingredients and materials for GMT+, and indicated initial consumer and provider acceptability prior to conducting a clinical trial.